Identifying brain systems for gaze orienting during reading: fMRI investigation of the Landolt paradigm - Hillen, Rebekka; Günther, Thomas; Kohlen, Claudia; Eckers, Cornelia; van Ermingen-Marbach, Muna; Sass, Katharina; Scharke, Wolfgang; Vollmar, Josefine; Radach, Ralph; Heim, Stefan (Frontiers in Human Neuroscience, 2013)
The Landolt reading paradigm was created in order to dissociate effects of eye movements and attention from lexical, syntactic, and sub-lexical processing. While previous eye-tracking and behavioural findings support the usefulness of the paradigm, it remains to be shown that the paradigm actually relies on the brain networks for occulomotor control and attention, but not on systems for lexical/syntactic/orthographic processing. Here, 20 healthy volunteers underwent fMRI scanning while reading sentences (with syntax) or unconnected lists of written stimuli (no syntax) consisting of words (with semantics) or pseudowords (no semantics). In an additional "Landolt reading" condition, all letters were replaced by closed circles, which should be scanned for targets (Landolt's rings) in a reading-like fashion from left to right. A conjunction analysis of all five conditions revealed the visual scanning network which involved bilateral visual cortex, premotor cortex, and superior parietal cortex, but which did not include regions for semantics, syntax, or orthography. Contrasting the Landolt reading condition with all other regions revealed additional involvement of the right superior parietal cortex (areas 7A/7P/7PC) and postcentral gyrus (area 2) involved in deliberate gaze shifting. These neuroimaging findings demonstrate for the first time that the linguistic and orthographic brain network can be dissociated from a pure gaze-orienting network with the Landolt paradigm. Consequently, the Landolt paradigm may provide novel insights into the contributions of linguistic and non-linguistic factors on reading failure e.g. in developmental dyslexia.